Effects of Crude Oil, Dispersant, and Oil-Dispersant Mixtures on Human Fecal Microbiota in an In Vitro Culture System - Jong Nam Kim (American Society for Microbiology, 2012)
ABSTRACT The Deepwater Horizon oil spill of 2010 raised concerns that dispersant and dispersed oil, as well as crude oil itself, could contaminate shellfish and seafood habitats with hazardous residues that had potential implications for human health and the ecosystem. However, little is known about the effects of crude oil and dispersant on the human fecal microbiota. The aim of this research was to evaluate the potential effects of Deepwater Horizon crude oil, Corexit 9500 dispersant, and their combination on human fecal microbial communities, using an in vitro culture test system. Fecal specimens from healthy adult volunteers were made into suspensions, which were then treated with oil, dispersant, or oil-dispersant mixtures under anaerobic conditions in an in vitro culture test system. Perturbations of the microbial community, compared to untreated control cultures, were assessed using denaturing gradient gel electrophoresis (DGGE), real-time PCR, and pyrosequencing methods. DGGE and pyrosequencing analysis showed that oil-dispersant mixtures reduced the diversity of fecal microbiota from all individuals. Real-time PCR results indicated that the copy numbers of 16S rRNA genes in cultures treated with dispersed oil or oil alone were significantly lower than those in control incubations. The abundance of the Bacteroidetes decreased in crude oil-treated and dispersed-oil-treated cultures, while the Proteobacteria increased in cultures treated with dispersed oil. In conclusion, the human fecal microbiota was affected differently by oil and dispersed oil, and the influence of dispersed oil was significantly greater than that of either oil or dispersant alone compared to control cultures. IMPORTANCE There have been concerns whether human health is adversely affected by exposure to spilled crude oil, which contains regulated carcinogens, such as polycyclic aromatic hydrocarbons. In this study, we determined the effect of BP Deepwater Horizon crude oil and oil dispersant on the human intestinal microbiota, since there is the potential that low-level residues of petrochemicals could contaminate seafood. The results of this study will increase our understanding of the ecophysiological changes in the microbial communities of the human gastrointestinal tract with respect to crude oil exposure.